2019
DOI: 10.21527/2317-5389.2019.14.187-200
|View full text |Cite
|
Sign up to set email alerts
|

Tráfico De Pessoas: Uma Análise Da Lei Nº 13.344/2016 À Luz Dos Direitos Humanos

Abstract: RESUMOA presente produção busca tratar do tema tráfico de pessoas sob a nova ótica da Lei N. 13.344 de 2016, especialmente sob suas novas formas de proteção e prevenção do crime, com o objetivo de compreender de que modo esse novo regulamento retrata disposições de cunho internacional e constitucional na medida de coibir violações a direitos humanos, em especial a dignidade humana. Tratando, então, das previsões de direitos humanos contra tráfico de pessoas, assim como as novas diretrizes, princípios e estrutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results found corroborate those reported by Alves (2014) which revealed that in areas where high unemployment rates prevail, activities related to wild animal trafficking can be very profitable, causing the rate of these crimes to increase. In another perspective, the economic development index of a region does not influence the decrease in animal trafficking, as happens in several Brazilian states, due to a tradition and popular culture of capturing wild animals to keep them as pets (Santos et al, 2018;Chaves and Devezas, 2019;Oliveira, 2019;Mendes, 2020;Almeida and Calandrini, 2021;Araujo, 2021;Wyatt et al, 2022), to use them for medicinal purposes, in religious rituals, as well as hunting as a sport or for food, and also trade to supplement income (Reis, 2014;Santos et al, 2018;Silva, 2018;Cavalcanti and Nunes, 2019;Oliveira, 2019).…”
Section: Cipoma 2022mentioning
confidence: 99%
See 1 more Smart Citation
“…The results found corroborate those reported by Alves (2014) which revealed that in areas where high unemployment rates prevail, activities related to wild animal trafficking can be very profitable, causing the rate of these crimes to increase. In another perspective, the economic development index of a region does not influence the decrease in animal trafficking, as happens in several Brazilian states, due to a tradition and popular culture of capturing wild animals to keep them as pets (Santos et al, 2018;Chaves and Devezas, 2019;Oliveira, 2019;Mendes, 2020;Almeida and Calandrini, 2021;Araujo, 2021;Wyatt et al, 2022), to use them for medicinal purposes, in religious rituals, as well as hunting as a sport or for food, and also trade to supplement income (Reis, 2014;Santos et al, 2018;Silva, 2018;Cavalcanti and Nunes, 2019;Oliveira, 2019).…”
Section: Cipoma 2022mentioning
confidence: 99%
“…The convention, directly and indirectly, incorporates everything that concerns biodiversity, operating as a kind of legal and political outline for the other more peculiar environmental conventions and agreements (Reis, 2014;Souza, 2017;Trajano and Carneiro, 2019;Araujo, 2021). As for the legislation, in Brazil, there is the Environmental Crimes Law nº 9.605/98 and the National Environmental Policy nº 6.938/81 (Cunha et al, 2014;Reis, 2014;Souza, 2017;Cavalcanti and Nunes, 2019;Chaves and Devezas, 2019;Silva, 2018;Vaz, 2018;Trajano and Carneiro, 2019;Araujo, 2021;Braga Junior and Lima, 2021;Silva, 2021;Menezes and Fontgalland, 2022;Sales et al, 2022), which addresses fauna as an environmental resource.…”
Section: Cipoma 2022mentioning
confidence: 99%